Production of non-food feedstock based biodiesel using acid-base bifunctional heterogeneous catalysts: A review. (15th April 2022) - Mulyatun, M.; Prameswari, Jedy; Istadi, I.; Widayat, W.
Graphical abstract: Highlights: Highlights current technologies on acid-base bifunctional heterogeneous catalysts. Producing high FFA non-food feedstock-based biodiesel from vegetable oils. Simultaneous esterification-transesterification reaction for biodiesel production. Processing high FFA oil using acid-base bifunctional catalyst (Bronsted-Lewis). Abstract: Research on biodiesel production utilizing heterogeneous catalysts continued to be studied as an effort to develop sustainable production and to improve the quality of biodiesel. The type of raw material and catalyst is considered as the main factors influencing the productivity and sustainability of the biodiesel process. Non-food feedstocks are considered as promising raw materials as they effectively reduced biodiesel production cost by 60–70%, in addition to the acid-base bifunctional heterogeneous catalyst that has garnered great attention due to its low cost, high reusability property, ability to process high free fatty acid (FFA) feedstocks, and only requiring one simple reaction step under moderate reaction conditions instead of the two separate esterification and transesterification reactions in biodiesel production. This review article highlighted that heterogeneous mixed-metal-oxide catalysts can be made to have bifunctional properties of the acid-base properties, depending on the types of metals and preparation method. This review would map current technologies on acid-base bifunctional heterogeneous catalyst able to process high free FFA feedstocks and stimulates future ideas in acid-base bifunctional catalyst development particularly in biodiesel production.